Islamophobia and the challenge of being Muslim in institutions of higher learning in Zimbabwe - Mabvurira, Vincent; Yasin, Adam (Penerbit Universiti Kebangsaan Malaysia, 2023)
With the rise of extremist and terror activities by the various groups which are alleged to be associated with Muslim religion, people of non-Muslim communities hold a negative perception about Islam and Muslims. This study examined challenges faced by Muslim students in two public universities in Zimbabwe. The study was informed by the Social Dominance Theory. Eighteen Muslim students participated in the study, and they were identified through purposive sampling from students’ religious societies. The findings revealed that Islamophobia in public universities has resulted in Muslim students facing various challenges that include stigmatization and labelling, institutional and religious discrimination, being denied their religious rights such as performing their prayers and their societies not being recognised as official religious society at the institutions whilst other faiths and religions are awarded that opportunity. The participants also pointed out that they encounter hate crimes and verbal abuse in the lecture rooms. Students from minor religions therefore face grievous challenges in public space in Zimbabwe where the majority of the population claim to subscribe to Christian faith. The study proffers several recommendations among them; universities should investigate discrimination on grounds of religious affiliation, conducting awareness campaigns to benefit minority religious groups and sensitising university staff to be religiously conscious in their conduct.